Analysis of The Effect of Energy Consumption, Economic Growth, And Trade Openness on Carbon Emissions: A Case Study of Indonesia 2003-2023 - Farida Nur Amalina (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
This study aims to analyze the influence of energy consumption, economic growth, and trade openness on carbon emissions in Indonesia. The research issue arises from the significant increase in Indonesia's carbon emissions over the past two decades, which has contributed to climate change, environmental degradation, and various sustainability challenges. As one of the developing countries with rapid economic growth, Indonesia faces the dual challenge of maintaining economic expansion while reducing environmental pressure. To address this issue, the study applies a quantitative approach using the Partial Adjustment Model (PAM) regression technique to examine the dynamic relationship between the selected variables. The analysis is based on annual time series data from 2003 to 2023, obtained from credible sources such as Statistics Indonesia (BPS), the World Bank, and the International Energy Agency (IEA). The findings reveal that energy consumption has a negative and statistically significant effect on carbon emissions, indicating an improvement in energy efficiency and a gradual transition towards renewable energy sources. Meanwhile, economic growth has a positive and significant impact on carbon emissions, suggesting that Indonesia's economic activities remain highly dependent on fossil fuels. In contrast, trade openness shows a positive but insignificant effect on carbon emissions. Overall, the study underscores the urgent need for integrated policies promoting green energy transition, sustainable trade, and low-carbon economic strategies to achieve environmentally responsible and sustainable long-term growth in Indonesia. Keywords: Carbon Emissions, Energy Consumption, Trade Openness, Economic Growth, PAM